Pragmatic reconstruction in jurisprudence. Features of a realistic legal theory - Tamanaha, Brian Z. (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
A century ago the pragmatists called for reconstruction in philosophy. Philosophy at the time was occupied with conceptual analysis, abstractions, a priori analysis, and the pursuit of necessary, universal truths. Pragmatists argued that philosophy instead should center on the pressing problems of the day, which requires theorists to pay attention to social complexity, variation, change, power, consequences, and other concrete aspects of social life. The parallels between philosophy then and jurisprudence today are striking, as I show, calling for a pragmatism-informed theory of law within contemporary jurisprudence. The realistic theory outlined in this essay focuses on what law does, what law is used for, what people think of law, how they act in relation to law, and what the social consequences of law are. It portrays law as a complex of institutions that evolve over time in connection with surrounding social, cultural, economic, political, technological, and ecological factors. Drawing on pragmatism, this essay sets forth the epistemological, ontological, and methodological aspects of the realistic theory of law, along with a sampling of insights that differ from or challenge widely held positions within jurisprudence. The topics covered, in order, are pragmatism, reconstruction in jurisprudence, naturalism, historicism and holism, social construction of law, and instrumentalism, power, and ideals.